Five great short stories - London, Jack, 1876-1916. (New York : Dover Publications, 1992)
A collection of five short stories by Jack London that reveal the harshness of the frozen wilderness of the Klondike.
The white silence -- In a far country -- An odyssey of the north -- The seed of McCoy -- The Mexican.
"A new selection of five unabridged stories"--Series t.p.
Adult
Keywords: Adventure fiction; Short stories; Klondike River Valley (Yukon) -- Fiction